Birthing outcomes and experience of holistic approach in women undergoing trial of labor after cesarean: a retrospective analysis - Gautham, Kavitha; Iyyer, Swarna Ganesan; Thiruvengadam, Nalini; Viswanathan, Ramya; P., Jeeshia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: A person-centered holistic birth approach (HBA) includes preparation of mind and spirit along with physical body to help mothers attain their ideal birthing experience. There is paucity availability of research done to evaluate the integrity of HBA. The present study aims to evaluate the birthing experience and outcomes of women undergoing a person-centered naturopathic pregnancy care. Methods: Women with at least one previous cesarean section with no significant comorbidity and spontaneous conception who opted to have holistic approach towards trial of labor after cesarean (TOLAC) (n=44) in a private birthing center with an exclusive birthing team located in Chennai were provided with evidence based holistic interventions under a naturopathic physician from 28 weeks of gestation till delivery. Data collected between November 2022 to September 2023 were analysed retrospectively for maternal and labor outcomes using descriptive statistics. Results: Out of all eligible pregnant women who had holistic approach (n=44), 1 in 2 (n=27) (61%) had successful vaginal birth (VB), women who came in labor spontaneously were n=32 (73%). Among those who delivered vaginally (n=27), n=17 (63%) had natural birth with no medical interventions, n=25 (93%) had nonmedicated pain management, n=16 (59%) had natural tears ranging from intact perineum to 2nd degree perineal tear and n=17 (46%) chose various birthing positions. Majority of women rated their childbirth experience to be empowering and satisfactory n=35 (88%). Conclusions: The study demonstrates, that a holistic approach involving a multidisciplinary team in a specialty birthing center delivered by qualified professionals could result in above mentioned birthing experience and outcomes which in turn empowers women through a person-centered care.